2009
DOI: 10.1111/j.1365-4632.2009.03799.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary localized cutaneous amyloidosis: a sign of immune dysregulation?

Abstract: The manifestations of primary localized cutaneous amyloidosis (PLCA) are usually limited to the skin. The exact etiopathogenesis of PLCA has not been clearly elucidated yet. An increasing number of reports in the literature that associate PLCA with various autoimmune/immune disorders suggest that underlying immune-mediated factors may be implicated. We report a case of sarcoidosis and a case of IgA nephropathy in association with extensive macular amyloidosis, adding these two conditions to the list of other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…If amyloid deposits are identified, it is important to determine whether the amyloidosis is localized or systemic. Typical sites for localized amyloidosis include the skin , larynx , or urinary tract , which can include the renal pelvis, ureter, bladder, and urethra. Pulmonary nodules demonstrating amyloid are frequently localized deposits composed of light chains or transthyretin .…”
Section: Disease Overviewmentioning
confidence: 99%
“…If amyloid deposits are identified, it is important to determine whether the amyloidosis is localized or systemic. Typical sites for localized amyloidosis include the skin , larynx , or urinary tract , which can include the renal pelvis, ureter, bladder, and urethra. Pulmonary nodules demonstrating amyloid are frequently localized deposits composed of light chains or transthyretin .…”
Section: Disease Overviewmentioning
confidence: 99%
“…On the basis of a patient of PLCA having sarcoidosis and IgA nephropathy and increasing number of reports suggesting immune mediated factors, the possibility of autoimmune basis in a group of patients with extensive disease was also proposed. [18] Yet, its etiology still remains an enigma.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Dahdah et al . [5] also reported a case of co-existing macular form of PLCA and sarcoidosis. However, to our knowledge, this report is the first description of concomitant appearance of NPLCA and PS.…”
mentioning
confidence: 99%
“…We cannot state with certainty whether the occurrence of these two diseases was associated or independent, but Dahdah et al . [5] suggested that a subset of PLCA patients, especially those with extensive or atypical involvement, may have associated immune disorders. In our case, NPLCA and PS have been stable without subjective symptoms.…”
mentioning
confidence: 99%